2011
DOI: 10.2190/ag.72.4.a
|View full text |Cite
|
Sign up to set email alerts
|

Worry in Older Community-Residing Adults

Abstract: With rising longevity, increasing numbers of older people are experiencing changes in their everyday family and social life, changes in their financial status, and a greater number of chronic conditions affecting their health. We took the opportunity to explore these relationships with worry in a group of volunteer community-living elderly (n = 310). Findings showed that that those people under 75 years of age had a higher risk of worrying (OR = 1.8, 95% CI = 1.0-3.1) compared to the older age groups. Women wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…As expected, health emerged as an important factor for late-life affect and satisfaction in that, for example, more frequent visitation with physicians and (increases in) disability were both associated with greater fear (Brock et al, 2011). A pattern seen for the first time here was that being overweight may operate as a risk factor for end-of-life emotionality (steeper increases in sadness and steeper declines in happiness).…”
Section: The Role Of Sociodemographic Physical Health and Psychosocia...supporting
confidence: 67%
“…As expected, health emerged as an important factor for late-life affect and satisfaction in that, for example, more frequent visitation with physicians and (increases in) disability were both associated with greater fear (Brock et al, 2011). A pattern seen for the first time here was that being overweight may operate as a risk factor for end-of-life emotionality (steeper increases in sadness and steeper declines in happiness).…”
Section: The Role Of Sociodemographic Physical Health and Psychosocia...supporting
confidence: 67%
“…They also found that health‐related worry was approximately twice as high among older adults who had general anxiety disorder, further documenting an empirical link between health worries and anxiety in older adults. Other research found that those with chronic health conditions worried more than those with acute health conditions . This is particularly relevant for long‐term cancer survivors who may continue to experience chronic effects of cancer or its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-syndromal anxiety symptoms in late life are even more prevalent than formal anxiety disorders, with prevalence estimates ranging from 15% to 52.3% in community samples (Bryant et al ., 2008). There is a unique set of challenges associated with the assessment of anxiety in late life, including the co-occurrence of anxiety with physical health problems (e.g., Brock et al ., 2011; Murphy et al ., 2012), with other mental health problems such as depression (e.g., Cairney et al ., 2008), and with cognitive impairment (e.g., Yochim et al ., 2013). Such challenges highlight the necessity to use screening and assessment tools that are specifically designed for older adults and are well validated among older adult populations.…”
Section: Introductionmentioning
confidence: 99%